IMPLEMENTASI SISTEM PENDUKUNG KEPUTUSAN MENENTUKAN KARYAWAN TERBAIK MENGGUNAKAN METODE PROFILE MATCHING DAN MABAC (Studi Kasus: PT. Victory Offset Prima) - Ridwan Hidayat Tullah; Elfi Fauziah (OKTAL : Jurnal Ilmu Komputer dan Sains, 2022)
PT Victory Offset Prima Jl. Aria Jaya Santika Desa No. # 8, Pasir Bolang, Kec. Tigaraksa, Tangerang Regency, Banten 15720, is one of the companies engaged in the printing industry. Have a work appraisal evaluation for its employees to determine the best employees which is carried out every year. However, the assessment is still done manually and is sometimes not objective and takes quite a bit of time. So to solve the problems above, a web-based Decision Support System is needed using the PHP Programming Language and MySQL database as data storage media and the application of Profile Matching and MultiAttributive Border Approximation Area Comparison (Mabac) methods.